2018
DOI: 10.17265/2162-5263/2018.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Intercropping Maize with Cowpea and Fertilization with Clinoptilolite on Forage Yield and Quality

Abstract: Maize forage is poor in protein content which leads to low quality and nutritive value. Regarding the high feed costs of protein supplementations, legumes can be used in livestock nutrition for their high protein content, and thus, provide cost savings. In this study, maize (Zea mays L.) and cowpea (Vigna unguiculata L.) were intercropped in different sowing densities and fertilization with clinoptilolite and their monocropping equivalents were tested to determine the best intercropping system on forage yield … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…It usually acquires its high N needs from the soil, while forage cowpea mainly fulfills its needs from the biological N fixation [6,49]. Atmospheric N fixation by forage cowpea would, thus contribute to reducing the competition of both crops for soil-applied N, and therefore, allow maize to use more of this [10,36]. In addition, maize might also use some of the biologically fixed N from cowpea [50].…”
Section: Impact Of Nitrogen Schedulementioning
confidence: 99%
See 2 more Smart Citations
“…It usually acquires its high N needs from the soil, while forage cowpea mainly fulfills its needs from the biological N fixation [6,49]. Atmospheric N fixation by forage cowpea would, thus contribute to reducing the competition of both crops for soil-applied N, and therefore, allow maize to use more of this [10,36]. In addition, maize might also use some of the biologically fixed N from cowpea [50].…”
Section: Impact Of Nitrogen Schedulementioning
confidence: 99%
“…The integration of both cereals and legumes in the same cropping system gives many advantages to the farming practice, such as reducing the damage caused by pests, diseases and weeds, securing better financial stability for the farmers and improving soil fertility [6][7][8]. In addition, the morphological and physiological differences between the component Agronomy 2022, 12, 107 2 of 17 crops allow for their complementarity in using the environmental resources resulting in a better yield and land use efficiency [9,10]. Generally, cereal-legume intercropping systems are receiving increased attention in both developing as well as developed countries to attain sustainability in grain and forage production [11,12] while avoiding the degradation associated with the extensive use of non-renewable recourses [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this direction, suggested that suitable spatial arrangements are among the most important factors that enhance the superiority of intercropping between maize-legumes over the single maize crop. Hence, the pattern of intercropping should affect the growth and performance of cowpeas because it determines the optimal space available to them for meet their needs of various growth inputs [12,16].…”
Section: Introductionmentioning
confidence: 99%